Diet, nutrients and metabolism: Cogs in the wheel driving Alzheimer's disease pathology? - Creegan, Rhona; Hunt, Wendy; McManus, Alexandra; Rainey-Smith, S. (Cambridge University Press, 2015)
Alzheimer's disease (AD), the most common form of dementia, is a chronic, progressive neurodegenerative disease that manifests clinically as a slow global decline in cognitive function, including deterioration of memory, reasoning, abstraction, language and emotional stability, culminating in a patient with end-stage disease, totally dependent on custodial care. With a global ageing population, it is predicted that there will be a marked increase in the number of people diagnosed with AD in the coming decades, making this a significant challenge to socio-economic policy and aged care. Global estimates put a direct cost for treating and caring for people with dementia at $US604 billion, an estimate that is expected to increase markedly. According to recent global statistics, there are 35.6 million dementia sufferers, the number of which is predicted to double every 20 years, unless strategies are implemented to reduce this burden. Currently, there is no cure for AD; while current therapies may temporarily ameliorate symptoms, death usually occurs approximately 8 years after diagnosis. A greater understanding of AD pathophysiology is paramount, and attention is now being directed to the discovery of biomarkers that may not only facilitate pre-symptomatic diagnosis, but also provide an insight into aberrant biochemical pathways that may reveal potential therapeutic targets, including nutritional ones. AD pathogenesis develops over many years before clinical symptoms appear, providing the opportunity to develop therapy that could slow or stop disease progression well before any clinical manifestation develops.